Efforts to Increase Public Knowledge About First Aid in Burns in Tanjung Mulieng, Syamtalira Aron District - Syahabuddin; Ainil Yusra; Fitriani Agustina (Jurnal Health Sains, 2024)
People's habits in providing first aid for burns still need to be reviewed. Wrong habits can worsen the patient's condition and prolong the wound healing process. Preventing the risk of infection and the occurrence of further complications which can increase the risk of death and disability. The aim of carrying out activities is to increase people's knowledge and skills in helping themselves and their families in cases of burns. The activity method is education, demonstration and simulation of first aid for burns. The target audience for this community service activity is the residents of Tanjong Mulieng Village, Syamtalira Aron District, North Aceh Regency, totaling 29 subjects. Evaluate the success of education using knowledge instruments that are measured before and after the activity is carried out and increase skills using a first aid checklist for burns. The results obtained were a good increase in knowledge of 76%, and participants were able to correctly demonstrate first aid steps for minor burns. Increasing the community's ability to help themselves and their families can be achieved by providing education and demonstrating first aid for burns.